2022
DOI: 10.1002/cctc.202200861
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐Silica as a Cheap Carrier and Green Soft Ligand for Improved Ru‐catalyzed Hydroformylation

Abstract: Dodecacarbonyltriruthenium Ru3(CO)12 has been immobilized onto a biopolymer (chitosan) supported on SiO2 (Ch@SiO2) to give Ru−Ch@SiO2. Ch@SiO2 behaves as a soft, recoverable and bulky ligand allowing the stabilization of released Ru active species and preventing its irreversible reduction to Ru0. Under these conditions very high activity (TOF= 1086 h−1; TON=2749) and regioselectivity (n:iso=92 : 8) are obtained, surpassing that of the homogeneous Ru3(CO)12 counterpart. Spectroscopic studies have shown that Ru3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…This phenomenon has been also recently observed in hybrid organic/inorganic supports. 20 Valero et al 21 found that the size of the Pd particles formed on the γ-Al 2 O 3 surfaces increases as the OH content of γ-Al 2 O 3 surface decreases. Addou et al , 22 through simulations and experiments, revealed that the strong interaction between Pd with the surface hydroxyls of the TiO 2 support increases the surface diffusion barriers and suppresses Pd particles from sintering.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been also recently observed in hybrid organic/inorganic supports. 20 Valero et al 21 found that the size of the Pd particles formed on the γ-Al 2 O 3 surfaces increases as the OH content of γ-Al 2 O 3 surface decreases. Addou et al , 22 through simulations and experiments, revealed that the strong interaction between Pd with the surface hydroxyls of the TiO 2 support increases the surface diffusion barriers and suppresses Pd particles from sintering.…”
Section: Introductionmentioning
confidence: 99%